Trends and Maps of Research Collaboration on Teacher Digital Literacy and Student Digital Citizenship: Bibliometric Analysis - Tita Setiawati; Atep Sujana; Rama Wijaya Abdul Rozak; Cica Yulia; Elih Sudiapermana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to identify trends, main topics, and patterns of scientific collaboration in the study of teachers' digital literacy and students' digital citizenship. Using bibliometric methods, this study analyzed scientific publications obtained from the Scopus database during the period 2016–2025. The data collected includes information about titles, authors, year of publication, keywords, affiliations, and journal sources. The analysis was conducted using VOSviewer software to map collaboration networks between researchers and between countries, as well as identify keywords that frequently appear in related publications. The results of the study show that teachers' digital literacy is a topic that has experienced a significant increase, especially since 2020, in line with the increasing need for digital learning during the pandemic. Meanwhile, studies on student digital citizenship are still relatively few but show a steady upward trend. The most frequently appearing keywords include